Photocatalytic Oxidation of 2-Butanol over Co3O4-Al2O3 Spinel Catalyst - Hussein I. Ismael (Journal of Global Pharma Technology, 2016)
The catalyst Co3O4-Al2O3 was prepared by co precipitation methods in different ratios (40: 60, 50: 50, 60: 40,70:30) for the mixed oxides respectively, these ratios were calcinated at 550 °C for 4hours and characterized by using powder X-Ray Diffraction, Fourier transform Infrared spectroscopy. These catalytic activity were investigated in photo oxidation of 2-butanol by using 0.2g.of Co3O4-Al2O3 in different times (0, 15,30,45,60 and 75 min). The result showed that the best ratio gives high activity was 40:60 at 25 °C. The resultant 2-butanone was measured spectrophotometrically at λ maximum=285nm and estimate this concentration depending on the calibration curve of 2-butanone.Keywords: Cobalt Oxide, Photooxidation of 2-butanol.